The role of Majelis Ta'lim Kanzul Ulum in improving Religious Knowledge in Karyamulya Village, Kesambi District, Cirebon City - Nurhaemin Nurhaemin; Dian Dinarni (The Future of Education Journal, 2024)
The role of majelis ta'lim Kanzul Ulum in improving religious knowledge in the village of Karyamulya Cirebon city is as a forum for coaching and development of spiritual knowledge in the field of morals, as a forum for the dimensions of Science and practice in terms of social rituals and as a potential developer and a forum for friendship that instills Sharia on adherence to Islamic teachings for Jama'ah, as a developer of Islamic religious education teachings contained in the Qur'an for Jama'ah. The moral consciousness of adolescents is built on existing religious knowledge. Supporting and inhibiting factors of majelis ta'lim Kanzul Ulum in improving religious knowledge in Karyamulya Village, Kesambi District, Cirebon City, among others, for supporting factors including the implementation of recitation activities at night, supported by the local government, invitation, carried out regularly according to the specified time, governance in place, strong tolerance, food availability. As for the inhibiting factors, work and daily schedule factors are related to distance and location factors and arise from the impact of media and technology developments.